Development and validation of promoter prediction system for recombinant lipase expression in Pichia pastoris - Gogo, Mayaki Fatima (2017)
One of the most reliable methods to improve the heterologous protein production is by conducting molecular cloning and expression of a targeted gene in an organism. This process requires extensive assessment on different promoters and hosts resulting in wastage of time, energy and resources. BLAST heuristic algorithm can predict lipase expression in Pichia pastoris. This study aims to develop a promoter prediction system for recombinant lipase expression in commonly used yeast expression system, P. pastoris using BLAST heuristic algorithm. Published experimental results of lipase expressed in P. pastoris were curated manually from publicly available databases and used for lipase database development. Two databases were developed, to store, organize and manage the curated data using MySQL and protein sequences in FASTA format using flat file. As for prediction, a BLAST heuristic method was implemented for sequence alignment and similarity comparison using Perl scripting language. The prediction system consists of two modules; Lipase Expression Database (LipExDB) and Lipase Expression Prediction System (LipExPS). LipExDB is a module for storing curated data and providing users with interface to query and retrieve information; and LipExPS is a module for users to upload the query sequence and retrieve the results of sequence alignment and other statistical parameters such as percentage of similarity and e-value. A user interface was provided for LipExPS. ARM lipase was used to validate the LipExPS. The predicted result of ARM lipase was used to clone into pGAPZαA and pPICZαB vectors followed by transformation into P. pastoris. The expression of ARM lipase was monitored in P. pastoris strain GS115. Based on the experimental validation, ARM lipase was successfully expressed in P. pastoris strain GS115 using GAP and AOX promoters as predicted by LipExPS. LipExPS was able to address the problem of promoter/host choice in lipase expression when using P. pastoris as a host by predicting the promoters that can be used to express the gene submitted to LipExPS. LipExDB would provide researchers with more information on lipase expression in P. pastoris. The development of this prediction system would facilitate the expression of lipase gene in P. pastoris thus saving resources, time and energy.